2001
DOI: 10.1046/j.1365-2141.2001.03148.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intramuscular therapy with Erwinia asparaginase and asparaginase Medac: pharmacokinetics, pharmacodynamics, formation of antibodies and influence on the coagulation system

Abstract: Asparaginase comes from different biological sources and the various preparations have different pharmacokinetic properties, and their tendency to induce side-effects is different. Erwinia asparaginase (ASNase) has a shorter half-life than the Escherichia coli preparations, and it has been reported to be less immunogenic than the E. coli preparations and to induce fewer coagulation disorders. Children with newly diagnosed acute lymphoblastic leukaemia (ALL) were included in this study. Twenty-seven patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 25 publications
1
48
2
Order By: Relevance
“…Although Erwinia asparaginase was first introduced into clinical trials in the early 1970s, 49 prior clinical pharmacokinetic studies of this preparation of the enzyme are limited to only two investigations involving relatively small patient numbers. 17,18 The time course of serum asparaginase activity resulting from intramuscular injection of a single 25 000-IU/m 2 dose of Erwinia asparaginase to pediatric ALL patients was first reported by Asselin et al 17 They found that the mean terminal phase half-life of asparaginase activity was 15.6 6 3.1 hours for intramuscular Erwinia asparaginase in 10 patients. In our study, the overall mean apparent biological half-life of asparaginase activity for the entire group of 54 patients with evaluable course 1 pharmacokinetic data was 16.5 6 6.4 hours, in excellent agreement with this value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Erwinia asparaginase was first introduced into clinical trials in the early 1970s, 49 prior clinical pharmacokinetic studies of this preparation of the enzyme are limited to only two investigations involving relatively small patient numbers. 17,18 The time course of serum asparaginase activity resulting from intramuscular injection of a single 25 000-IU/m 2 dose of Erwinia asparaginase to pediatric ALL patients was first reported by Asselin et al 17 They found that the mean terminal phase half-life of asparaginase activity was 15.6 6 3.1 hours for intramuscular Erwinia asparaginase in 10 patients. In our study, the overall mean apparent biological half-life of asparaginase activity for the entire group of 54 patients with evaluable course 1 pharmacokinetic data was 16.5 6 6.4 hours, in excellent agreement with this value.…”
Section: Discussionmentioning
confidence: 99%
“…18 Asparaginase activity decayed with a mean half-life of 6.4 6 1.9 hours when the enzyme was given by the intravenous route. The mean total body clearance of Erwinia asparaginase was 0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This cut-off of ≥ 0.1 IU/mL has been confirmed and used in many clinical trials. 9,19,[22][23][24] The question arises whether a lower threshold, for example of 0.05 IU/mL, also leads to complete asparagine depletion. Rizzari and colleagues showed that trough asparaginase activity levels of < 0.05 IU/mL, obtained either with native E. Coli or Erwinia asparaginase, resulted in serum and CSF asparagine depletion in children with ALL.…”
Section: What Defines Optimal Asparaginase Activity?mentioning
confidence: 99%
“…This leads to inadequate plasma levels of the EcA, which limit its efficacy. However, it was reported that not all patients with hypersensitivity develop ADAs, and not all patients who develop ADAs exhibit hypersensitivity (16,17). Another serious drawback of the anti-leukemic drugs is their generalized cytotoxic effects on healthy cells along with leukemic cells.…”
mentioning
confidence: 99%